Smart materials and nanotechnology in engineering : selected, peer reviewed papers from the 2011 International Conference on Smart Materials and Nanotechnology in Engineering (SMNE 2011), September 17-18, 2011, Wuhan, China - Zhong, J. L. (Advanced materials research ;, 2012)
This volume comprises a collection of the papers presented at the 2011 International Conference on Smart Materials and Nanotechnology in Engineering (SMNE2011), held on September 17~18th, 2011, in Wuhan, China. The aim was to provide a platform where researchers, engineers, academics and industrialists from all over the world could present research results and developments in Smart Materials and Nanotechnology in Engineering. This makes the work an eminently up-to-date guide to those fields. Review from Book News Inc.: This volume collects 160 papers presented at the International Conference o.